2021
DOI: 10.4103/sjg.sjg_530_20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of colorectal cancer: A five-gene prognostic signature based on RNA-binding proteins

Abstract: Background: Colorectal cancer (CRC) is one of the most common cancers worldwide. RNA-binding proteins (RBPs) regulate essential biological processes and play essential roles in a variety of cancers. The present study screened differentially expressed RBPs, analyzed their function and constructed a prognostic model to predict the overall survival of patients with CRC. Methods: We downloaded CRC RNA-sequencing data from the Cancer Genome Atlas (TCGA) portal and screened d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…NAT10 and CSE1L have already been involved in COREAD ( Sillars-Hardebol et al, 2012 ; Tai et al, 2013 ; Zhang et al, 2014 ; Liu et al, 2016 ; 2019 ; Pimiento et al, 2016 ; Cao et al, 2020 ; Xu et al, 2020 ). NOP56 and RBM12 were already identified in COREAD by different data mining approaches ( Liang et al, 2021 ), validating our results. Additionally, to the best of our knowledge, no prior studies have associated FKBP1A and EMG1 with cancer before.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…NAT10 and CSE1L have already been involved in COREAD ( Sillars-Hardebol et al, 2012 ; Tai et al, 2013 ; Zhang et al, 2014 ; Liu et al, 2016 ; 2019 ; Pimiento et al, 2016 ; Cao et al, 2020 ; Xu et al, 2020 ). NOP56 and RBM12 were already identified in COREAD by different data mining approaches ( Liang et al, 2021 ), validating our results. Additionally, to the best of our knowledge, no prior studies have associated FKBP1A and EMG1 with cancer before.…”
Section: Discussionsupporting
confidence: 89%
“…In COAD, we identified two RBPs (NAT10 and NOP56) having all four tumor-associated characteristics presented in this study. NAT10 has already been implicated in colorectal cancer in several studies ( Zhang et al, 2014 ; Liu et al, 2016 ; 2019 ; Cao et al, 2020 ), while NOP56 has been found differentially expressed in COREAD by a different data mining approach ( Liang et al, 2021 ). Also, we were able to retrieve two other RBPs (RBM12 and FKBP1A) that were not essential for tumor cell survival, but they could be implicated in any other hallmark of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Kaplan–Meier survival plots, receiver operating characteristic (ROC), C-index and DCA curves, visualized by R package“survival”, “timeROC”,“ggDCA” and “survminer”, were used to evaluate prognostic value of risk model in colon cancer. The constructed model in this study was also compared with known models in predicting the prognosis of colon patients ( Huang et al, 2018 ; Li et al, 2021 ; Liang et al, 2021 ). Univariate and multifactor analyses were performed to determine the independent prognostic value of the risk model.…”
Section: Materials Methodsmentioning
confidence: 99%
“…Likewise, IGF2BP3 is involved in constructing prognostic models of colorectal cancer. Liang et al screened and identified five RNA-binding protein-related prognostic signatures from TCGA (IGF2BP3, PABPC1L, PPARGC1A, PTRH1, and TDRD7) [85]. Busuioc et al found that the epithelial-mesenchymal transition gene signature can predict the overall survival rate of colon adenocarcinoma patients (NOX4, IGF2BP3, DACT3, EEF1A2, BMP5, GCNT2, and SFRP1) [86].…”
Section: Colorectal Cancermentioning
confidence: 99%